Improving the Students’ Ability in Using the Expression of “Asking for and Giving Information by Using Chit Chat Strategy at the Seventh Grade of SMPN I Semanding - Maskuri, Moch (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2016)
This research aims to describe the process of improving the studentsÃ¢â‚¬â„¢ competence in expressing Ã¢â‚¬Å“asking for and giving information and to know the studentsÃ¢â‚¬â„¢ achievement in expressing Ã¢â‚¬Å“Ã¢â‚¬Âasking for and giving information at the seventh grade of SMP N I Semanding, Tuban. This research is carried by using classroom action research. The subject of the study is class A of seventh grade of SMP N I Semanding, Tuban. The writer only takes class A that consists of 30 students. In conducting the research, the writer uses the procedure of classroom action research. They are planning, Acting, Observing and Reflecting. In collecting the data the writer uses the following procedures: Conducting the observation and giving test. In analyzing the data the writer uses the procedure of collecting data. they are describing the process of improving the studentsÃ¢â‚¬â„¢ competence, correcting the students test, and describing the studentsÃ¢â‚¬â„¢ achievement. Based on the research result, it is found that the process of improving the studentsÃ¢â‚¬â„¢ competence in expressingÃ¢â‚¬Âasking for and giving informationÃ¢â‚¬Â is done in two cycles. In cycle 1, the students had not been able to achieve Ã¢â‚¬Å“KKMÃ¢â‚¬Â (kriteria kelayakan minimal). Then the writer continouses the second cycle. Finally all students Achieved Ã¢â‚¬Å“KKMÃ¢â‚¬Â. Based on the result of the test, it is found that some of the students had not been able to achive Ã¢â‚¬Å“KKMÃ¢â‚¬Â at first cycle. Then, the writer did the second cycle. Based on the test result of second cycle, it is found that all students had achieved more than 65. It is the score of Ã¢â‚¬Å“KKMÃ¢â‚¬Â. The varage score is 73,5. It is categorized as good. It can be concluded that chit-chat game can improve the studentsÃ¢â‚¬â„¢ ability of the seventh grade of SMP N I Semanding, Tuban in expressing Ã¢â‚¬Å“asking for and giving informationÃ¢â‚¬Â